Recurrence of Pemphigus Vulgaris Under Nivolumab Therapy - Krammer, Sebastian; Krammer, Christian; Salzer, Suzanna; Bağci, Işin Sinem; French, Lars E.; Hartmann, Daniela (Frontiers in Medicine, 2019)
For many types of cancer, immune checkpoint inhibitors have proven to be a highly effective treatment. The monoclonal anti-PD-1 antibody nivolumab stimulates the immune system and is one of the newest treatment options for non-small cell lung cancer. In doing so, immune checkpoint inhibitors can trigger many skin lesions that have not yet been completely investigated in their entirety. In this case report, pemphigus vulgaris is identified as a potential adverse event that occurs under the treatment with nivolumab. In addition to the standard methods, we examined our patient's samples with ex vivo confocal laser scanning microscopy. This is a new and innovative diagnostic method that uses vertical scanning to provide fast, high-resolution imaging of freshly excised tissue, even using fluorescently labeled antibodies.